INCIDENCE OF INSECT PESTS ON RICE CROP UNDER VARIOUS NITROGEN DOSES - M. Ramzan; S. Hussain; M. Akhter (Journal of Animal and Plant Sciences, 2007)
To investigate the effect of different doses of Nitrogen fertilizer on the incidence of rice insect pests, the experiments were conducted at six locations. The lowest percent infestation of stem borers was recorded in the treatment where nitrogen was not applied at all but the yield was also adversely affected. The pest incidence in LCC based N application treatment was at par with the treatments without Nitrogen with highest yield. The crop with 120 Kg/ha nitrogen application showed highest susceptibility to insect pests with the highest pest incidence. There was significant yield improvement in LCC based nitrogen application (92 Kg N/ha). With further increase in N (100Kg/ha) the yield became stagnant and at 120 Kg N/ha, it start declining but remained at par with LCC based N application. The results further reveal that excessive use of N fertilizers to the crop is the wastage of resources that pose serious effects on crop health in the form of pest incidence. Optimizing the dose of nitrogen in relation with other macronutrients and its split applications are extremely essential because high nitrogen makes tissue vulnerable to pest attack.
Keywords: Pests; Rice; Nitrogen fertilizer; stem borer; basmati